Impact Assessment of Entrepreneurial Skills Acquisition Programme on Agropreneurial Skills of National Youth Corps Members in Ile Ife, Osun State, Nigeria - Oyebola, Abiodun Isaac (Future Science / FSH-PH Publications, 2024)
The rampaging food insecurity around the globe and particularly in Nigeria despite the availability of suitable land mass for agriculture and the teeming youthful population raised concern for the study. The possibility of exploring the opportunity provided by the National Youth Service Corps in reorientating Nigeria graduates in agropreneurship using a self-developed manual necessitated the study. The study employed pretest posttest design. Convenient sampling technique was employed in sampling 73 corps members who were serving in Ile Ife and its environs. Agropreneurship Interest Scale (AIS) a self-developed 20-item likert-type questionnaire was used for data gathering. The content validity ratio (α = 1) and reliability coefficient (r = 0.89) respectively were obtained for the instrument. Analysis of data showed that participants had low interest in agropreneurship (18.33%) before the commencement of the training. Also, that the training has significant impact on the agropreneurship interest of the participants (mean learning gain of the participant = 67.89%). The study concluded that Nigeria youths particularly the Corpers can be effectively motivated in agropreneurship using appropriate manual and strategies.